Optimizing Civil Construction Litigation In Indonesia: A Comprehensive Framework For Efficiency, Expertise, And Equity In Dispute Resolution - Azizan, Akmal; Sophia, Sally; Zahra, Salma; Perai, Nurajam (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2024)
Delays, excessive expenses, and a decline in public confidence come from the specialized nature of civil construction litigation in Indonesia. Several efforts have been made to improve civil construction litigation in Indonesia, such as introducing procedural reforms to expedite case processing times, increasing access to mediation and alternative dispute resolution (ADR), and the occasional involvement of technical experts to assist judges in understanding complex construction issues.Â Â Unresolved problems continue despite current attempts; a complete system redesign is required. This paper attempts to fill such knowledge gaps and provide fresh approaches to civil construction litigation in Indonesia. This study provides a comprehensive strategy to improve litigation effectiveness, efficiency, and professionalism by incorporating worldwide best practices and offering practical solutions. The research takes a methodical look at effective models in the UK, Germany, France, and Japan. It identifies critical issues in the Indonesian setting and develops specialized procedural tools like